Biomass carbon stock assessment of mangrove ecosystem in Pannikiang Island South Sulawesi Indonesia - Abdul Malik; Uca Sideng; Jaelani Jaelani (Indonesian Journal of Geography, 2022)
One of the essential services provided by mangroves is carbon sequestration, and therefore climate change mitigation. While previous assessments of mangrove carbon stocks and sequestrations have focused on the estuarine and deltaic mangrove setting, there are still limited studies carried out at small island mangroves. The study aims to assess mangrove biomass carbon stocks in Pannikiang, a small island in South Sulawesi, Indonesia, which occupies 91.64 ha of species-rich pristine mangrove forests. A field-based data collection survey was performed using a circular plot approach, while above-ground tree carbon (AGC) and below-ground root carbon (BGC) stocks were estimated using available species-specific allometric equations. The mean AGC and BGC were 5.34 ± 0.17 and 1.68 ± 0.04 Mg C ha-1, respectively. Bruguiera gymnorrhiza mangrove species stored the greatest of carbon stocks, followed by Scyphiphora hydrophyllacea. Carbon stocks obtained from small island mangroves in this study were lower than stocks assessed from other mangrove locations across Indonesia and Southeast Asia. However, historical rates of deforestation in Pannikiang Island may generate emissions to approximately 82.17 Mg CO2-eq. Findings from this study will be beneficial in providing baseline data for policy decision-making on climate change mitigation in the region, specifically for improved land use management via a low carbon development agenda.